Flubber - Hughes, John; Mestres, Ricardo; Mayfield, Les (USA : Walt Disney Pictures [production company] ; Kuala Lumpur : Berjaya HVN [distributor])
Flubber - Disney's high-flying smash hit comedy that stretches all boundaries of the imagination
Executive producer, David Nichsay ; editor, Harvey Rosenstock, Michael A. Stevenson
Cast : Robin Williams, Marcia Gay Harden, Christopher Mc Donald
Keywords: Comedy films; Fantasy comedies (Motion pictures); Children's films